Assessment of Renal Function in Women with Preeclampsia by Measuring of Serum Cystatin C Level - Marwa Basim Yarmurad; Miami Abdul Hassan Ali (Mustansiriya Medical Journal)
Background: Preeclampsia (PE) is a major health problem that increases the risk of renal impairment during pregnancy. Studies have described the utility of Cystatin C as a better indicator of kidney function during pregnancy compared to urea, creatinine, or uric acid. Objective: The objective of the study was to evaluate cystatin C as a diagnostic tool for renal impairment in women with severe PE and compare it to standard renal function tests. Patients and Methods: A case–control study was conducted at Al Yarmouk Teaching Hospital, Bagdad. From March 1, 2022, to September 1, 2022, 94 3rd-trimester pregnant women with newly diagnosed or a history of PE were included in the study and interviewed and subsequently divided into three groups. The GraphPad Prism Software was used for data analysis and graphical presentations in addition to SPSS version 28; 0.05 was selected as a cutoff point for statistical significance. Results: The mean of cystatin C for control 0.39 ± 0.15 was significantly lower than for severe PE 1.12 ± 0.53, P < 0.001. The mean cystatin C for mild PE 0.52 ± 0.13 was considerably lower than for severe PE 1.12 ± 0.53, P < 0.001. Conclusions: Patients with severe PE had higher serum cystatin C than patients with mild PE and healthy normotensive pregnant females. Serum cystatin C at a cutoff value of >0.61 had higher diagnostic accuracy than the other standard kidney tests (urea, creatinine, and uric acid), with a sensitivity and specificity of 90.32% and 93.75%, respectively.